What homoeopathy has to offer in the rare disease scenario of India: an overview - Kumat, Omkar R.; Kundu, Tapas Kumar; Kundu, Rita Tapas; Kalda, Prapti J. (International Journal Of Community Medicine And Public Health, 2025)
Incidences of rare diseases (RDs) are subsequently increasing in India. The cost of the treatment involved is exorbitant and therefore it becomes difficult for the patient to afford it. So, the need of the hour is to implement health care policies that are in favor of both, the patients and the government. Keeping in mind the current scenario of the RDs in India this article is written to mitigate this problem as far as possible using the homoeopathic system of medicine. This article delineates a newer approach to RD treatment programs available. Homoeopathy in haemophilia (HIH) research center established in the year 2007, had provided homoeopathic treatment to more than 1300 people with haemophilia i.e. 5.27% according to the annual global survey 2021, where the total number of registered haemophilia patients in India were 25384. Homoeopathy had proven over the years that it works by interacting with the genetic code of the patient. Also, it is based on the principles of symptom similarity rather than disease diagnosis. This makes it more applicable for patients of RDs because it relieves the symptoms and reduces their severity until the proper diagnosis and treatment are provided. Homoeopathy had proved itself to be a cost-beneficial therapy for patients with hemophilia and so this could be the pilot study for the other genetic diseases too.